2021
DOI: 10.12659/msm.930046
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Water-Soluble Contrast Medium Gastrografin in Treatment of Adhesive Small Bowel Obstruction in Patients with and Without Chronic Radiation Enteropathy: A Single-Center Retrospective Study

Abstract: Background This retrospective cohort study from a single center aimed to compare patient outcomes following the use of the water-soluble contrast medium Gastrografin in the treatment of adhesive small bowel obstruction (ASBO) in patients with and without a history of chronic radiation enteropathy (CRE). Material/Methods Fifty-nine patients with CRE-induced small bowel obstruction (SBO) and 53 patients with ASBO at Jinling Hospital between April 2014 and February 2018 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A recent retrospective study reported that patients with ASBO who underwent NGT-G treatment had initial surgery and re-operation rates of 41.4% and 11.2%. 6 Although their patient background and study design differed from the current study, our treatment strategy achieved much better 1-year surgery rates. This may be due to the careful observation and switching to LT even when colonic contrast was observed at 24 h. ASBO recurrence frequently occurs due to the inability of non-surgical treatment to resolve itself.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A recent retrospective study reported that patients with ASBO who underwent NGT-G treatment had initial surgery and re-operation rates of 41.4% and 11.2%. 6 Although their patient background and study design differed from the current study, our treatment strategy achieved much better 1-year surgery rates. This may be due to the careful observation and switching to LT even when colonic contrast was observed at 24 h. ASBO recurrence frequently occurs due to the inability of non-surgical treatment to resolve itself.…”
Section: Discussionmentioning
confidence: 61%
“…2 The present study found no significant differences in 1-year recurrence rates between both groups. The most recent latest retrospective study reported a recurrence rate of 41.9% during 1-year follow-up, 6 whereas another recent retrospective study found a 21.3% overall recurrence risk following non-surgical management (during a median follow-up interval of 3.6 years). 9 In line with this, the current study observed a recurrence rate of around 30%, which was within the range of previously published findings.…”
Section: Discussionmentioning
confidence: 97%
“…The studies span an 11‐year period from 2010 to 2021. The studies included 54 retrospective cohort studies [17–70], eight prospective cohort studies [4, 71–77], seven RCTs [78–84], and four retrospective case–control studies [85–88]. 45 studies were single centre, 20 utilised databases and 8 were multicentre.…”
Section: Resultsmentioning
confidence: 99%
“…The only probable explanation found is because of its high osmolality, it allows the shifting of fluid into the bowel lumen, decreasing edema and diluting bowel content for easy passage. As described above, it also aids in the need's evaluation for surgery in bowel obstruction [11]. Our study aims to evaluate the diagnostic and therapeutic value of gastrografin in adhesive intestinal obstruction.…”
Section: Introductionmentioning
confidence: 96%